PENINGKATAN PEMASARAN UMKM JAYA SEBLAK 06 MELALUI PEMANFAATAN GOOGLE MAPS DAN E-COMMERCE DI DESA SUKAMAKMUR - Alfa Khair; Amanda Adelia; Laila Rahmayuni Rangkuti; Misrah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of Google Maps and e-commerce in improving marketing effectiveness at Jaya Seblak 06 MSME in Sukamakmur Village, Langkat Regency. The research is motivated by the low level of digital literacy and limited marketing reach among MSMEs in rural areas. A qualitative descriptive method was applied, with data obtained through field observations, interviews, and documentation of digitalization assistance activities. The results indicate that before digital implementation, the marketing strategy was conventional and limited to local consumers. After adopting Google Maps and e-commerce, there was a significant improvement in business visibility, market reach, and sales volume. Google Maps functions as a location-based promotional tool that enhances business credibility and accessibility, while e-commerce platforms expand market coverage and simplify online transactions. In addition, social media such as TikTok also plays a supportive role in strengthening brand image and promoting products to a wider audience. Overall, the integration of these digital technologies creates an efficient, adaptive, and sustainable marketing system. The findings confirm that digital transformation is an essential factor in strengthening competitiveness and ensuring the sustainability of MSMEs in the technology-driven economy era.